Barriers and Facilitators to the Implementation and Adoption of a Continuous Quality Improvement Program in Surgery: A Case Study. Issue 4 (10th October 2022) - ElChamaa, Rima; Seely, Andrew J.E.; Jeong, Dahn; Kitto, Simon
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: As postoperative adverse events (AEs) drive worsened patient experience, longer length of stay, and increased costs of care, surgeons have long sought to engage in innovative approaches aimed at reducing AEs to improve the quality and safety of surgical care. While data-driven AE performance measurement and feedback (PMF) as a form of continuing professional development (CPD) has been presented as a possible approach to continuous quality improvement (CQI), little is known about the barriers and facilitators that influence surgeons' engagement and uptake of these CPD programs. The purpose of this knowledge translation informed CPD study was to examine surgeons' perspectives of the challenges and facilitators to participating in surgical CQI with the broader objective of enhancing future improvements of such CPD interventions. Methods: Using Everett Rogers diffusion of innovations framework as a sampling frame, the participants were recruited across five surgical divisions. An exploratory case study approach, including in-depth semistructured interviews, was employed. Interview transcripts were analyzed and directly coded using the Theoretical Domains Framework. Results: Directed coding yielded a total of 527 coded barriers and facilitators to behavior change pertaining to the implementation and adoption of PMF with the majority of barriers and facilitators coded in four key theoretical domains environmental context and resources, social influences, knowledge, and beliefs about consequences. A key barrier was the lack of support from the hospital necessitating surgeons' self-funding their own PMF programs. Facilitators included having a champion to drive CQI and using seminars to facilitate discussions around CQI principles and practices. Discussion: This study identified multiple barriers and facilitators to surgeons' engagement and uptake of a data-driven PMF system in surgery. A key finding of the study was the identification of the influential role of positive deviance seminars as a quality improvement and patient safety mechanism that encourages surgeon engagement in PMF systems.